Asthma phenotypes and associated comorbidities in a large cohort of adolescents in Israel. (2nd July 2020) - Machluf, Yossy; Farkash, Rivka; Rotkopf, Ron; Fink, Daniel; Chaiter, Yoram
Abstract: Objectives: Asthma is a multifactorial, heterogeneous, complex and common chronic respiratory disease driven by diverse mechanisms. Although asthma presents various clinical forms with different levels of severity, it is unclear whether asthma severities are a consequence of disease management or varied etiologies. We sought to investigate this question. Methods: This article presents a cross-sectional study of 113, 671 Israeli adolescents. Univariate and multivariable logistic regression models were performed to analyze the independent associations between mild asthma and moderate-to-severe asthma phenotypes and coexistent medical conditions within each gender separately. Hierarchical clustering of the odds ratios of the diverse statistically significant medical conditions associated with asthma severity-gender groups was also performed. We focused on the allergic and neurological-cognitive-mental disorders. Results: Among males, two associations were common to both asthma groups (atopic dermatitis and allergic rhinitis), five unique to mild asthma (urticaria/angioedema, Hymenoptera/bee allergies, allergic conjunctivitis, epilepsy and migraine) and two unique to moderate-to-severe asthma (learning disabilities and ADD/ADHD (Attention-deficit disorder/Attention-deficit/hyperactivity disorder)). Among females, two associations were common to both clinical asthma groups (allergic rhinitis and urticaria/angioedema), and five unique to moderate-to-severe asthma (atopic dermatitis, learning disabilities, ADD/ADHD, anxiety/mood disorders and migraine). Allergic rhinitis was the only condition to be associated with all four groups. Learning disabilities and ADD/ADHD were only associated with moderate-to-severe asthma (but not with mild asthma), in both males and females. Hierarchical clustering analysis uncovered two prominent clusters, separating mild from moderate-to-severe asthma. Conclusions: The differences between mild and moderate-to-severe asthma enhance asthma phenotype characterization, with respect to comorbidities, and indicate varied etiologies.